NO2 gas sensor based on QCM coated with iron oxide nanorods - Vinh, Nguyen Thanh; Phan, Vu Ngoc; Nam, Man Hoai; Tuan, Le Anh; Quy, Nguyen Van (Vietnam Journal of Science and Technology, 2020)
Iron oxide nanorods were synthesized by chemical co-precipitation method. The structural and morphological characteristics of the as-synthesized nanorods were analyzed by X-ray diffraction (XRD) and scanning electron microscopy. The results show that the iron oxide nanorods include the mixture of Fe3O4, γ-Fe2O3 and FeOOH with the diameter and the length of iron oxide nanorods to be 30 nm and 100 nm, respectively. The iron oxide nanorods were then dispersed and deposited on the gold electrode of quartz crystal microbalance (QCM) for the gas sensing application. The iron oxide nanorods based QCM sensor was tested with various concentrations of numerous toxic gases at room temperature, including nitrogen dioxide (NO2), sulfur dioxide (SO2), ammonia (NH3), and carbon monoxide (CO). The testing results indicate that fabricated sensor exhibits high performance to NO2 in the concentration range from 5 ppm to 20 ppm.